Analysis of the Content and Accuracy of Multicultural Values in Islamic Religious Education and Moral Textbook - Hajiannor Hajiannor; Kundharu Saddhono; Elihami Elihami; Musyarrafah Sulaiman Kurdi; Muqarramah Sulaiman Kurdi (STAI Hubbulwathan Duri, 2023)
This study aims to analyze the content of the developed multicultural values and the accuracy of the development of multicultural values with the components of Islamic Religious Education and Morals textbooks for class VIII. This type of research is qualitative with a library approach. Data were collected by reviewing documents, namely Islamic Religious Education and Moral textbooks for class VIII junior high school. Data analysis techniques include content analysis and critical analysis. Checking the validity of the findings is done by means of triangulation techniques. This study concludes that the content of multicultural values developed in the textbook is four values, namely tolerance, democracy, justice, and equality. The accuracy in developing multicultural values in the textbook component is said to be inaccurate because the percentage is 35.8%. Thus, there are multicultural values in Islamic Religious Education and Moral textbook, but the content needs to be developed proportionally.